Mental Health–Ill Health Differences in Disease Severity and Its Sociodemographic Biobehavioral Predictors Among Patients With Knee Osteoarthritis. (September 2019) - Rezakhani Moghaddam, Hamed; Nadrian, Haidar; Abbagolizadeh, Nategh; Babazadeh, Towhid; Aghemiri, Mehran; Fathipour, Asaad
Our aim in this cross-sectional study was to investigate mental health–ill health differences in disease severity and its sociodemographic biobehavioral predictors among patients with knee osteoarthritis (OA). Applying convenient sampling, 180 patients with knee OA in Tabriz, Iran, were recruited to participate in completing a three-section questionnaire (SF-12, Lequesne Algofunctional Index and Self-Management Behaviors Scale). Separate hierarchical multiple linear regressions were performed with OA severity as dependent variable: one for OA patients with positive mental health and other for OA patients with mental disorders symptoms . Among the patients with positive mental health, but not those with symptoms of mental disorder, pain management, duration of OA, physical activity management, living alone, and level of education were significant predictors of disease severity. Health care providers with a better understanding on the determinants of disease severity by mental health status may identify vulnerable patients and develop targeted interventions to foster disease management behaviors among OA patients.